2003
DOI: 10.1016/s1471-4922(03)00190-9
|View full text |Cite
|
Sign up to set email alerts
|

Performance of forecasting, warning and detection of malaria epidemics in the highlands of western Kenya

Abstract: On the 4th July 2002 a leading national newspaper in Kenya, the Daily Nation, ran the headline 'Minister sounds alert on malaria' in an article declaring the onset of epidemics in the highlands of western Kenya. There followed frequent media coverage with quotes from district leaders on the numbers of deaths, and editorials on the failure of the national malaria control strategy. The Ministry of Health made immediate and radical changes to national policy on treatment costs in the highlands by suspending cost-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…This shows for the first time that climate forecasts may usefully extend the early warning available from environmental monitoring on a continental scale and reaffirms the potential importance of accurate climate information in Africa (Thomson et al 2011). It is important to emphasize that this study is a first step and is 1994Alonso et al (2011 Higher than usual transmission indicated in Kenyan highlands 1998 Lindblade et al (1999) Epidemic starts in Feb in Ugandan highlands; authors associate outbreak with rainfall anomalies 1998 Githeko and Ndegwa (2001) Epidemic in Kenya from Feb 1998, but high incidence also reported in Jun-Jul 1997Jones et al (2007 Epidemic in Tanzania highlands from Feb to Jun 1998, and high incidence also reported in summer of 1997 2002 Hay et al (2003a) Epidemic identified in Nandi and Kericho in Jun-Jul, with conditions returning to normal in August; normal transmission occurred in the Kisii and Gucha districts 2005 Cox et al (2007) Examines DHIS data from 2002 to 2006 for Kabale and identifies outbreaks in 2005 (timing not described) and 2006 (centered on Jun) but questions the authenticity of the latter outbreak by using confirmed data from a sentinel site 2010 Ototo et al (2011) Report vector densities over the period from Sep 2009 to Apr 2010, reporting peak vector densities in Jan-Feb 2010; no long-term dataset is available to determine whether conditions were anomalous 2010 Yeka et al (2012) Describes general transmission in Uganda; smear-positivity rates for children under 5 show relative peaks in Kanungu District (Kihihi) for Oct-Dec 2009 and May-Jul 2010 (their Fig. 4); no anomalies in selected high-transmission zones limited to identifying the potential skill in such a system.…”
Section: Discussion: Integrating Climate Information Into Health Planmentioning
confidence: 67%
See 3 more Smart Citations
“…This shows for the first time that climate forecasts may usefully extend the early warning available from environmental monitoring on a continental scale and reaffirms the potential importance of accurate climate information in Africa (Thomson et al 2011). It is important to emphasize that this study is a first step and is 1994Alonso et al (2011 Higher than usual transmission indicated in Kenyan highlands 1998 Lindblade et al (1999) Epidemic starts in Feb in Ugandan highlands; authors associate outbreak with rainfall anomalies 1998 Githeko and Ndegwa (2001) Epidemic in Kenya from Feb 1998, but high incidence also reported in Jun-Jul 1997Jones et al (2007 Epidemic in Tanzania highlands from Feb to Jun 1998, and high incidence also reported in summer of 1997 2002 Hay et al (2003a) Epidemic identified in Nandi and Kericho in Jun-Jul, with conditions returning to normal in August; normal transmission occurred in the Kisii and Gucha districts 2005 Cox et al (2007) Examines DHIS data from 2002 to 2006 for Kabale and identifies outbreaks in 2005 (timing not described) and 2006 (centered on Jun) but questions the authenticity of the latter outbreak by using confirmed data from a sentinel site 2010 Ototo et al (2011) Report vector densities over the period from Sep 2009 to Apr 2010, reporting peak vector densities in Jan-Feb 2010; no long-term dataset is available to determine whether conditions were anomalous 2010 Yeka et al (2012) Describes general transmission in Uganda; smear-positivity rates for children under 5 show relative peaks in Kanungu District (Kihihi) for Oct-Dec 2009 and May-Jul 2010 (their Fig. 4); no anomalies in selected high-transmission zones limited to identifying the potential skill in such a system.…”
Section: Discussion: Integrating Climate Information Into Health Planmentioning
confidence: 67%
“…In particular, Rogers et al (2002) highlighted the potential role of satellite monitoring of climate conditions in early-warning systems for malaria and called for improvements in disease-modeling capabilities to fulfill this potential. Hay et al (2003a) also affirmed that rainfall monitoring could lead to improved planning potential. This was demonstrated in a case study for the Kenyan highlands, which also showed that the seasonalforecast models at the time were inadequately skillful to extend the advance warning provided by rainfall observations (Hay et al 2003b).…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Although studies have identified important climatic, seasonal, and demographic factors underlying large-scale spatial and temporal patterns of malaria epidemics in African countries, [6][7][8][9][10][11][12][13] thus far, attempts to develop predictive models of malaria epidemics, which are accurate on the local scale, have not met with success. 14,15 At present, there are few small-scale temporal-spatial studies of malaria incidence, particularly in urban highland area of Africa. Small-scale temporal-spatial studies of malaria transmission are therefore essential to target interventions toward transmission hot spots, which may shift seasonally within a given locale.…”
Section: Introductionmentioning
confidence: 99%